Trade and equilibrium among the ALADI countries - Jorge Torres Zorrilla; Eduardo Gana (CEPAL Review, 1985)
The Latin American economic crisis, basically caused by the adjustment of the external sector with a view to generating surpluses to service the debt with the international financial system, has had a powerful adverse effect on the trade flows of the ALADI countries. Nevertheless, an effective co-operation among them is now more necessary than ever in order to overcome the external bottleneck and restore the levels of intra-zonal trade. The reactivation of zonal trade should, moreover, generate additional trade on a relatively more balanced and stable basis than in the past, through the multilateral linkages within the zone.